Mise en œuvre concertée et solidaire du Protocole de Nagoya et du Traité international sur les ressources phytogénétiques: scénarios à considérer par les points focaux nationaux et autres parties prenantes intéressées. - Joint Capacity Building Programme (2017)
Bioversity International works with a wide range of international and national partners to implement the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty) and the Nagoya Protocol of the Convention on Biological Diversity in mutually supportive ways.